Effects of patient deterioration simulation using inattentional blindness for final year nursing students: A randomized controlled trial. (November 2021) - Park, Jaewon; Kim, Kyoung-Ja
Abstract: Background: Patient deterioration should be detected early and responded appropriately for patient safety. It is necessary to strengthen situational awareness regarding patient deterioration. Inattentional blindness is a major factor that hinders situational awareness about patient deterioration in the clinical setting. Objectives: To analyze the impact of patient deterioration simulation using inattentional blindness (PDS-IB) on situational awareness and patient safety competency-attitude among final year nursing students. Design: A randomized controlled trial. Participants: Final year nursing students at a university in South Korea. Methods: Students were randomly assigned to an experimental or control group. The experimental group (n = 47) was given a PDS-IB. The control group (n = 44) received a simple patient deterioration simulation. Situational awareness and patient safety competency-attitude were measured at baseline, post intervention, and at 2 weeks follow-up. Data were analyzed using a two-way repeated measures ANOVA. Results: There were statistically significant group effects, time effects, and group and time interaction effects in situational awareness and patient safety competency-attitude. Conclusion: PDS-IB is an effective educational strategy that increases situational awareness and patient safety competency-attitude in final year nursing students. Highlights: Inattentional blindness (IB) is critical. Patient deterioration simulation using IB is developed. PDS-IB is effective to SA and PSC-A.